INFLUENCE OF SEX ,SPAWNING STARVATION AND WATER TEMPERATURE ON FATTY ACID COMPOSITION IN TILAPIA MOSSAMBICA. - NAIR, K. G RAMACHANDRAN; GOPAKUMAR, K (Fishery Technology, 2017)
The influence of sex, spawning, starvation and water temperature on the fatty acid composition of Tilapia mossambia has been studied. Tilapia egg lipid was found to have unusually high percentage of C22:6 fatty acids (9.09 %) compared to body and intestinal lipids. The C16:1 acid was much less in the egg lipids (3.5 %) whereas it was 11 % in the body lipids. There was no significant difference in the fatty acid composition of body and intestinal lipids of male and female tilapia.. . Starvation caused the presence of high content of lower fatty acids (C6, C8, C30, C12 and C33) in the body lipids. Water temperature also influenced the fatty acid composition of Tilapia; the difference was more significant in body lipids than in intestinal lipids.